Pelatihan Pembuatan Nanas Toga sebagai Upaya Pemberdayaan Perempuan di Desa Gunungjaya - Devia Arbarista Rismawati; Yulia Cahyaningrum; M Fikri Amrullah; Sugeng Riyadi (Jurnal Dharma Indonesia, 2026)
This community service activity aims to optimize the potential of pineapples in Gunungjaya Village by developing "Nanas TOGA" health drinks to enhance economic value and women's empowerment. The primary issues partners faced were the low selling price of raw pineapples and a lack of post-harvest processing skills. The implementation method included observation, four product formulation trials, packaging training, and legal assistance for business operations. The results demonstrated an increase in the partners' capacity for standardized pineapple processing diversification. The primary outputs achieved were: 1) "Nanas TOGA" health drink products ready for market; 2) Brand identity design and product labeling; and 3) Acquisition of a Business Identification Number (NIB) as business legality facilitated through coordination with the Diskoperindag of Pemalang Regency. The program's success is measured by the formation of a micro-business unit within the PKK community, capable of transforming agricultural commodities into value-added products while strengthening women's roles as sustainable local economic drivers.